Active Tectonic and Mechanic Interaction Between Cusiana and Yopal Faults Interpreting Seismic and Terraces Geometry. Issue 1 (1st December 2016) - Torres, J.S. Carvajal; Costantino, D.; Gómez, J. F.; Reyes, M.; Mora, A.
Abstract : Along the Colombian Llanos Foothills, different rock formations lie affected by tectonic movements, expressing geomorphological changes at the surface associated with subsurface geologic structures (anticlines and synclines). Some of them were created during the most recent tectonic movements throughout the last period of geological time. This evidence is plotted in the geological map of the area extended from the Colombian Eastern Cordillera to the Colombian Llanos Orientales basin (figure 1). There, folded and faulted Quaternary deposits can be observed. This is the case of the alluvial terraces in the study area (figure 1), which have been deformed due to the recent tectonic activity. Therefore, to test this theory, this study generates a three dimensional kinematic model based on serial balanced geological cross sections built by seismic, geological and well data. Hence, we can analyze the geometry of faults in the area (Cusiana and Yopal), with the geometry of the Alluvial Terraces deposited during the Late Pleistocene (0.2 Ma, ICP, (2009)). Consequently, it simulates the fault kinematics since the Quaternary Terraces deposition in order to quantify fault motion rates, thereby, assessing the age of faulting. Finally, in addition, this study, using PetroMod 1D models, appraises the age of the famous Colombian oil field called Cusiana. As a result, it demonstrates the continuous generation and migration of oil from the kitchen located at the Colombian Eastern Cordillera, to the Colombian Llanos Basin.